IMPLEMENTASI KEBIJAKAN PELAYANAN TERPADU SATU PINTU (PTSP) PADA PLATFORMELEKTRONIK JAKARTA EVOLUTION (JakEVO) DI KOTA JAKARTA TIMUR - Agus Sjafari; Anisa Putri Ramdani (LPPM STIA Banten, 2023)
In order to provide comprehensive transparency and convenience to the community in service activities, the Provincial Government of DKI Jakarta issued Regulation of the Governor of DKI Jakarta Province No. 47 of 2017 concerning Guidelines for Implementing One-Stop Integrated Services The government is innovating an electronic platformto implement One-Stop Integrated Services online, named Jakarta Evolution (JakEVO). One of the areas in DKI Jakarta that is actively participating in organizing One Stop Integrated Services (PTSP) is the City of East Jakarta. This study uses the public policy implementation model according to Charles O. Jones (1996), namely Organization, Interpretation, and Application (Implementation). This study uses qualitative methods, by collecting data through observation, interviews, and documentation. The data analysis technique used is proposed by Miles and Huberman (1984). The results of the study show that the Implementation of the One Stop Service Policy (PTSP) on the Jakarta Evolution Electronic Platform(JakEVO) in East Jakarta City has not been maximized. This can be seen starting from the existence of a platformowned by the Central Government, namely OSS (Online Single Submission) which is similar to JakEVO, the limited Human Resources it has, the authority for One Stop Integrated Services has not been fullyhanded over to UP PMPTSP in East Jakarta City, so that it has not socialization directly to the community.